Constraints on Non-Radial Oscillation Modes by Symmetry Energy Slope - 周颖 文德华 (Communications in theoretical physics, 2014)
The effect of the nuclear symmetry energy slope on the non-radial oscillation f-modes in neutron stars is calculated and discussed. Based on a conservative range of the symmetry energy slope constrained by the experiment and theoretical analysis, a constraint on the frequency and damping time of the gravitational radiation from the f-mode in neutron star is obtained. It is also shown that a higher symmetry energy slope corresponds with a smaller frequency and a longer damping time. Meanwhile, a new set of parameters is given to present the universal properties of the scaled frequency and damping time.